Implementation Role of HR in Organizational Transformation as Agent of Change - Shinta Ratnawati; Hanung Eka Atmaja; Budi Hartono (Jurnal Ekonomi dan Bisnis, 2021)
An organizational transformation that results in "dramatic" events that must be addressed by all members of the organization. This study uses three basic theories from Kurt Lewin that explain the process of change in an organization, namely unfreezing, movement, and refreezing. The phenomenon that occurs at Tidar University as a new university is the optimization of human resources towards Indonesia 2045. Humans with self empowerment and flexibility as agents of change in developing management strategies for successful organizational performance towards equality with other PTN. This research was conducted to examine the implementation of the role of professional resources on organizational transformation as an agent of change. This research was conducted through a literature study that refers to research and critical review of previous theories. As for the relevance of our data, we distributed questionnaires to 25% of the total employees as baseline deep in interviews in group discussions to share professional experiences, understand our own assumptions and assumptions of others and to understand the profession. The analysis uses Lewin's three-step process approach to agents of change in change in organizations. In a critical review change management has a constructive framework for managing organizational change through the process phase. The results of this study provide theories and practical implications of a process of change by the "agent of change".